The lifeguard - Blumenthal, Deborah (2012)
Spending the summer at her aunt's beach house, teenaged Sirena struggles with her parents' divorce and falls in love with a mysterious lifeguard.
Keywords: Romance fiction; Divorce -- Juvenile fiction; Beaches -- Juvenile fiction; Young adult fiction; Paranormal fiction